2015
DOI: 10.1093/nop/npv033
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with reporting guidelines by Australian pathologists: an audit of the quality of histopathology reporting in high-grade glioma

Abstract: Background Diagnostic pathology reports inform management plans for patients with glioma, and there is an increasing clinical need for molecular testing. We assessed the quality of histopathology reports of grade III/IV gliomas. Methods Reports were obtained as part of a tumor biobank. From 720 pathology reports, 594 eligible reports were assessed for 28 elements derived from published checklists. A summary quality score inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…A quality score incorporating critical parameters for clinical decision makingfor example, type and grade of tumour, up-to-date classification, absence of equivocal languageshould be introduced and adopted by national and international committees. Recently an audit conducted by Australian pathologists found that report quality was higher when pathologists subspecialised in neuropathology [41] and that only 24% of reports fulfilled all quality criteria.…”
Section: Pathology Reportingmentioning
confidence: 99%
“…A quality score incorporating critical parameters for clinical decision makingfor example, type and grade of tumour, up-to-date classification, absence of equivocal languageshould be introduced and adopted by national and international committees. Recently an audit conducted by Australian pathologists found that report quality was higher when pathologists subspecialised in neuropathology [41] and that only 24% of reports fulfilled all quality criteria.…”
Section: Pathology Reportingmentioning
confidence: 99%